1981
DOI: 10.1073/pnas.78.4.2522
|View full text |Cite
|
Sign up to set email alerts
|

Effect of agents that produce membrane disorder on lysis of erythrocytes by complement.

Abstract: To evaluate the effect of membrane lipid acylchain packing on the efficiency of cell lysis by complement, we have studied membrane modulation by 2-(2-methoxy)-ethoxyethyl-8-(cis-2-n-octylcyclopropyl)-octanoate (A2C) and by myristoleyl alcohol, the cis isomer of a C14:1 aliphatic alcohol. These substances are known to increase the membrane lipid disorder by virtue of the bend in their acyl chains, which is believed to loosen the phospholipid acyl-chain packing. We have found that both of these compounds markedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Membrane modulation by 2-(2methoxy)-ethoxyethyl-8-(cis-2-n-octylcyclopropyl)octanoate and by myristoleyl alcohol, which are known to increase membrane disorder by loosening the phospholipid acyl chain packing, was found to increase C lysis of erythrocytes by the terminal complement proteins C5b-9. 11 From a mechanistic view, assembly of the membrane attack complex involves the incorporation of hydrophilic molecules into a macromolecular amphiphilic complex capable of integrating into lipid bilayers. This integration should be much simpler when membrane fluidity is sufficiently high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane modulation by 2-(2methoxy)-ethoxyethyl-8-(cis-2-n-octylcyclopropyl)octanoate and by myristoleyl alcohol, which are known to increase membrane disorder by loosening the phospholipid acyl chain packing, was found to increase C lysis of erythrocytes by the terminal complement proteins C5b-9. 11 From a mechanistic view, assembly of the membrane attack complex involves the incorporation of hydrophilic molecules into a macromolecular amphiphilic complex capable of integrating into lipid bilayers. This integration should be much simpler when membrane fluidity is sufficiently high.…”
Section: Discussionmentioning
confidence: 99%
“…8,10 The influence of membrane disorder on C activation has also been addressed by Shin et al who found in a reactive lysis assay using sheep erythrocytes that 2-(2-methoxy)-ethoxyethyl-8-(cis-2-n-octylcyclopropyl)-octanoate and myristoleyl alcohol, which are known to increase membrane disorder, enhance C lysis. 11 Performing electrical measurements on a reconstitution model of the outer membrane of Gram-negative bacteria as asymmetric planar LPS/phospholipid bilayer, we were able to characterize pore formation by C in a very direct manner. 12,13 Thus, we recently characterized the structural requirements of the sugar moiety of the glycolipids for C activation.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of disruption of phospholipidcholesterol liposomes varies inversely with the concentration of membrane cholesterol (275), and there is a correlation between susceptibility of sheep erythrocytes to complement attack and the ratio of membrane lecithin to sphingomyelin (171), suggesting that increased membrane fluidity enables a more efficient assembly and integration of MACs on phospholipid membranes. Incorporation of the fluidizing and fusogenic agent 2-(2-methoxy)-ethoxyethyl-8-(cis-2-n-octylcyclopropyl)-octanoate into sheep erythrocyte membranes loosens phospholipid acylchain packing and thus increases membrane lipid disorder; cells treated in this way become extremely susceptible to complement lysis (274).…”
Section: Resistance To Serum Bactericidal Activity Definition Of Serumentioning
confidence: 99%
“…[6] Cationic lipids containing cis-unsaturated FAs can promote membrane lipid disorders by interacting with anionic phospholipids. [7] The fusion between two lipid membranesi sm ediated by al amellar-to-hexagonal inverted phase transition. [8] This process is promoted by cone-shapedc ationic lipids, where the cross-sectional area of the hydrophilic head groups is smaller than that of the hydrophobic tails.…”
Section: Introductionmentioning
confidence: 99%
“…Well‐known cationic lipids like DOPE, DOTMA and DOSMA contain the cis ‐unsaturated fatty acid (FA) oleic acid and were first used to efficiently delivery DNA and mRNA in 1987 and 1989, respectively . Cationic lipids containing cis ‐unsaturated FAs can promote membrane lipid disorders by interacting with anionic phospholipids . The fusion between two lipid membranes is mediated by a lamellar‐to‐hexagonal inverted phase transition .…”
Section: Introductionmentioning
confidence: 99%